Pengembangan Video Tari Kreasi Nusantara Anak Usia Dini Pada Pembelajaran Seni di TK Pandu Ilmi Persada - Estuhono, Estuhono; Ana Novitasari; Tirta Kencana Prima (Jurnal Tunas Pendidikan, 2025)
This research is motivated by the importance of developing creative dance arts in early childhood in the process of growth and development. Apart from that, dancing is needed to accommodate physical movements that are fun for children. The aim of this research is to develop Indonesian creative dance for early childhood in arts learning in TK Pandu Ilmi Persada. This type of research is research an development (research and development). The development model used is the field development model which consists of preliminary research stages, prototyping phase, assessment phase. To find out the results of the research on Indonesian creative dance that was developed, an assessment as carried out using validation, practicality and effectiveness sheets. The results of the assessment of early childhood Indonesian creative dances carried out by one expert had a score of 90% in the very valid category. The results of research on the implementation of Indonesian creative dance for early childhood in arts learning, which was assessed by the class teacher, had a score of 100% in the very practical category. The results of applying Indonesian creative dance to student obtained a percentage of 88,57% in the very effective category.